Preparation and Application of a MoN / WN / CoMoO4 / NF Three-Phase Mott-Schottky Heterojunction Electrocatalyst
Patent Information
- Application Number
- CN202611250067.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]针对上述现有技术中存在的缺陷,本发明提出了一种MoN/WN/CoMoO4/NF三相Mott-Schottky异质结电催化剂的制备及应用,旨在解决以下具体技术问题:(1)避免依赖贵金属原料,通过构建MoN/WN/CoMoO4/NF三相Mott-Schottky异质结构,利用多相界面协同效应,同步实现高效HER与UOR双功能催化,以克服单一组分或二元复合催化剂催化活性不足的缺陷;(2)利用MoN、WN氮化物与CoMoO4氧化物之间的功函数差异,构筑Mott-Schottky异质界面内建电场,优化界面电子传输速率,改善电化学反应动力学缓慢的问题;(3)采用泡沫镍基底原位生长工艺,制备无粘结剂自支撑电极,增强催化剂与基底之间的结合强度,克服粉末催化剂在大电流条件下易脱落、结构坍塌及稳定性差等不足;(4)获得可耐受安培级大电流的长效催化电极,满足工业尿素辅助电解制氢系统的连续运行需求,同步实现含尿素废水处理与低能耗绿氢制备
(1)本发明制备的三相异质复合电催化剂具备优异HER/UOR双功能电催化活性,两类半反应动力学速率显著提升。HER反应中,在1.0M KOH电解液内,达到50mA·cm-2、100mA·cm-2电流密度对应的过电位仅为50mV、73mV,Tafel斜率低至49mV dec-1;UOR反应中,在1.0MKOH+0.5M尿素电解液内,10mA·cm-2电流密度下电位仅1.29V vs RHE,Tafel斜率为42mVdec-1。搭建两电极尿素辅助电解制氢体系后,10mA·cm-2槽电压仅1.32V;在500mA·cm-2工业大电流密度工况下,相较于传统纯水OER电解体系,槽电压可降低456mV,大幅降低电解制氢能耗,同步实现尿素废水降解与绿氢制备。
Smart Images

Figure CN122918629A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalysis and green hydrogen production new energy materials technology, and particularly relates to the preparation and application of a MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst. Background Technology
[0002] Against the backdrop of global energy structure transformation, developing clean and low-cost green hydrogen production technologies is one of the important pathways to achieving carbon neutrality. Traditional water electrolysis for hydrogen production relies on the hydrogen evolution reaction (HER) at the cathode to generate hydrogen, but its oxygen evolution reaction (OER) at the anode involves a four-electron transfer process, resulting in slow reaction kinetics and a high overpotential, leading to a significant increase in energy consumption and hindering its large-scale application. The thermodynamic equilibrium potential of the urea oxidation reaction (UOR) (0.37V vs. RHE) is significantly lower than that of OER (1.23V vs. RHE). Therefore, using UOR instead of OER as the anode reaction can not only significantly reduce the electrolyzer voltage and save energy, but also simultaneously achieve the degradation treatment of urea-containing wastewater, combining the dual benefits of energy production and environmental remediation. This makes urea-assisted electrolysis hydrogen production technology a promising candidate for industrial application.
[0003] Currently, the core bottleneck limiting the development of urea-assisted electrolysis hydrogen production technology lies in the lack of highly efficient HER / UOR bifunctional electrocatalysts suitable for industrial-scale operating conditions. While noble metal catalysts, represented by Pt and Ru, possess excellent catalytic activity, their scarcity in the Earth's crust and high raw material costs make it difficult to meet the demands of large-scale industrial application. Existing non-noble metal catalytic materials also have significant technical limitations: single-component materials cannot simultaneously meet the different catalytic activity site requirements of both HER and UOR reactions; furthermore, most reported composite catalysts have only undergone performance verification in the low current density range (milliampere level). (At 500 mA·cm⁻¹) -2 At industrial-grade ampere-level high current densities of 1000 amperes and above, such catalysts generally face problems such as nanostructure collapse, dissolution or shedding of active components, and their long-term operational stability cannot meet the industrial requirements for continuous operation of electrolyzers.
[0004] Molybdenum-based transition metal materials are considered ideal alternatives to noble metal catalysts due to their abundant reserves and tunable electronic structure. Among them, MoN and WN have Pt-like d-electron configurations and exhibit outstanding intrinsic HER catalytic activity; however, they readily form inert oxide layers in anodic oxidation environments, leading to a significant reduction in their UOR catalytic activity. CoMoO4 molybdate contains abundant redox sites and possesses suitable adsorption strength for UOR reaction intermediates, resulting in excellent anodic catalytic performance; however, as a semiconductor material, it has weak intrinsic conductivity and a slow charge transport rate, making it difficult to efficiently drive the HER process. Therefore, none of the above single materials can independently achieve efficient bifunctional catalysis.
[0005] Studies have shown that constructing Mott-Schottky heterojunctions by utilizing the work function difference between the metal and semiconductor phases, and optimizing charge transport paths and synergistically regulating the adsorption energy of reaction intermediates through the built-in electric field at the interface, is an effective strategy to enhance the activity of bifunctional catalytic catalysts. However, most existing research is limited to the construction of binary composite systems, and no technical schemes have been reported that simultaneously introduce MoN and WN bisnitrides and couple them with CoMoO4 to form three-phase Mott-Schottky heterojunctions. In addition, existing research generally neglects industrial ampere-level high-current applications, and there is a lack of systematic research and evaluation on the long-term stability of catalysts at high current densities. Furthermore, most existing composite catalysts are in powder form, requiring the addition of binders for coating during use, which can easily lead to detachment and failure during long-term high-current electrolysis. Moreover, existing conventional synthesis processes are difficult to achieve in-situ preparation of integrated three-phase nanostructures on conductive substrates.
[0006] In summary, the existing technologies have the following drawbacks: (1) Pt and Ru-based bifunctional catalysts have excellent catalytic performance, but their reserves are scarce and the procurement costs are extremely high, making it difficult to promote them on a large scale in the industrial sector; conventional single MoN, WN, or CoMoO4 materials can only be adapted to HER or UOR reactions, and cannot simultaneously and efficiently catalyze two types of electrochemical reactions; (2) Existing binary composite catalytic systems can only construct a single heterogeneous interface, lacking a three-phase coupling structure of MoN, WN, and CoMoO4, resulting in limited interfacial electronic regulation capabilities, high charge transfer resistance, slow reaction kinetics, and significant catalytic decay under high current; (3) Most catalytic materials on the market are in powder form, and organic binders must be added during use; at 500 mA·cm -2 During the long-term electrolysis of the above industrial-grade high current, problems such as active material shedding, nano-skeleton collapse, and metal component dissolution are likely to occur, and the long-term stability cannot meet the requirements of continuous operation of the electrolyzer; (4) Most existing studies only verify the performance under small current of tens of milliamperes per square centimeter, lacking long-term stability studies for ampere-level industrial conditions, and cannot match the actual urea coupled hydrogen production production scenario. Summary of the Invention
[0007] To address the shortcomings of the existing technologies, this invention proposes a method for preparing and applying a MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst, aiming to solve the following specific technical problems: (1) Avoiding reliance on precious metal raw materials, by constructing a MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterostructure, utilizing the synergistic effect of multiphase interfaces, simultaneously achieving efficient HER and UOR bifunctional catalysis, thereby overcoming the shortcomings of insufficient catalytic activity of single-component or binary composite catalysts; (2) Utilizing MoN, WN nitrides and Co The difference in work function between MoO4 oxides is used to construct the built-in electric field of the Mott-Schottky heterostructure, optimize the interface electron transport rate, and improve the problem of slow electrochemical reaction kinetics; (3) The in-situ growth process of nickel foam substrate is used to prepare a self-supporting electrode without binder, enhance the bonding strength between the catalyst and the substrate, and overcome the shortcomings of powder catalysts such as easy detachment, structural collapse and poor stability under high current conditions; (4) A long-lasting catalytic electrode that can withstand ampere-level high current is obtained to meet the continuous operation requirements of the industrial urea-assisted electrolysis hydrogen production system, and simultaneously realize the treatment of urea-containing wastewater and the preparation of low-energy green hydrogen.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A three-phase Mott-Schottky heterojunction electrocatalyst of MoN / WN / CoMoO4 / NF is disclosed, using nickel foam as a conductive substrate, on which an array of nanorods is grown in situ. The nanorods are composed of a CoMoO4 semiconductor phase, MoN and WN metal nitride phases, and the Mott-Schottky heterojunction interface is constructed by the difference in work function between the nitrides and oxides.
[0009] This invention uses commercially available nickel foam as a conductive electrode substrate, and grows a cross-linked nanorod array in situ on its surface. The nanorods are composed of a CoMoO4 semiconductor phase and MoN and WN metal nitride phases. Utilizing the work function difference between the oxide and nitride phases, a Mott-Schottky heterojunction is constructed at the interface. Based on the difference in work function of each component, a built-in electric field is spontaneously formed at the heterojunction interface, driving the directional migration of electrons and thus optimizing the charge transport path. Simultaneously, the cross-linked nanorod array has a porous structure, endowing the electrode with an ultra-large electrochemical active area and superhydrophilic properties, which helps accelerate electrolyte penetration and promote timely desorption of reactant gases, effectively preventing the active sites from being shielded. Furthermore, the electrode prepared by the in-situ growth method has a self-supporting structure, requiring no binder, and the catalyst is firmly bonded to the nickel foam substrate, which is beneficial for improving structural stability under high current conditions.
[0010] Furthermore, the nanorod array is a cross-linked nanorod array, possessing a porous structure and superhydrophilic properties.
[0011] Beneficial effects: The porous structure significantly increases the electrochemical active area, providing more exposed catalytic active sites; the superhydrophilic properties promote the rapid penetration of electrolyte into the electrode interior, while also facilitating the timely desorption of gases generated in the reaction (H2, N2, CO2), preventing bubbles from obscuring active sites and improving mass transfer efficiency under high current density.
[0012] This invention also provides a method for preparing the above-mentioned MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst, comprising the following steps: (1) Cut the nickel foam substrate, and clean it with dilute hydrochloric acid, anhydrous ethanol and deionized water in sequence to remove the oxide layer and oil stains on the surface of the nickel foam, and then vacuum dry it. (2) Dissolve molybdate, tungstate and cobalt salt in deionized water and stir thoroughly until completely dissolved to obtain a mixture; completely immerse the pretreated nickel foam substrate from step (1) in the mixture and then place it in a reactor for hydrothermal reaction. After the reaction is completed, cool naturally to room temperature and wash the product with deionized water and anhydrous ethanol in sequence. After vacuum drying, obtain the CoMoO4 / WO3 / NF composite oxide precursor. (3) The CoMoO4 / WO3 / NF composite oxide precursor obtained in step (2) is placed together with urea in the reaction zone of a tube furnace. High-purity nitrogen is introduced throughout the process to maintain an inert protective atmosphere for high-temperature nitriding. After cooling, the MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst is obtained.
[0013] Beneficial effects: The process route of this invention is simple and the conditions are mild. It does not require precious metal raw materials and complex equipment, and it is easy to scale up production. In addition, urea serves as both a nitrogen source and a reducing atmosphere during the nitriding process, achieving the simultaneous conversion of molybdenum / tungsten oxides to nitrides in one step and efficiently constructing a three-phase heterogeneous interface.
[0014] Furthermore, in step (1), the ultrasonic cleaning time for dilute hydrochloric acid, deionized water, and anhydrous ethanol is 10 min; the vacuum drying temperature is 60~80℃.
[0015] Beneficial effects: It ensures that the oxide layer and oil stains on the surface of nickel foam are completely removed, resulting in a clean and activated substrate surface, which is conducive to the uniform and dense in-situ nucleation and growth of precursors and improves batch-to-batch consistency.
[0016] Further, in step (2), the molar ratio of molybdate, tungstate, and cobalt salt is 1:(0.1~0.4):(0.1~0.4).
[0017] Beneficial effects: Precise control of the three-phase composition ratio avoids catalytic performance imbalance caused by excess or deficiency of a single phase; within this range, the density of the three-phase heterogeneous interface can be maximized, achieving optimal synergy of HER and UOR dual-function activities.
[0018] Further, in step (2), the molybdate is ammonium molybdate, the tungstate is sodium tungstate, and the cobalt salt is cobalt nitrate.
[0019] Beneficial effects: The selected salts are all inexpensive and readily available conventional chemical reagents with good water solubility and moderate thermal decomposition temperature. They can stably release metal ions and transform them into the target phase during subsequent hydrothermal and nitriding processes, ensuring the controllability of the synthesis process and the purity of the product.
[0020] Furthermore, in step (2), the temperature of the hydrothermal reaction is 120~180℃, and the reaction time is 6~12h.
[0021] Beneficial effects: Under these mild conditions, CoMoO4 and WO3 precursors can be uniformly crystallized and grown in situ into nanorod arrays, while avoiding excessive grain growth or substrate corrosion caused by excessively high temperatures, ensuring that the morphology and crystal phase of the precursors meet the requirements of subsequent nitriding transformation.
[0022] Furthermore, in step (3), the heating rate during the high-temperature nitriding process is 3~5℃ / min, the holding temperature is 500~700℃, and the holding time is 2~4h.
[0023] Beneficial effects: Slow heating ensures uniform heating of the precursor and avoids structural cracking; precise control of nitriding temperature and time can completely convert some Mo / W oxides into MoN and WN nitride phases while retaining the CoMoO4 oxide phase, achieving coexistence of three phases and clear heterogeneous interfaces, while ensuring that the overall morphology of the nanorod array does not collapse.
[0024] The present invention also provides a two-electrode electrolysis system for urea-assisted electrolysis to produce hydrogen, in which the above-mentioned MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst is used as both the cathode and anode.
[0025] Beneficial effects: The use of the same electrode material to efficiently drive HER and UOR at the cathode and anode respectively simplifies the electrolyzer structure design, avoids matching and compatibility issues caused by using two different catalysts, reduces assembly costs, and both electrodes have excellent mechanical strength and chemical stability.
[0026] Furthermore, the two-electrode electrolysis system is electrolyzed in an alkaline electrolyte containing urea, with hydrogen evolution occurring at the cathode and urea oxidation occurring at the anode.
[0027] Beneficial effects: The thermodynamic potential of UOR is much lower than that of OER, which can significantly reduce cell voltage and save energy; at the same time, it utilizes the anodic reaction to degrade urea-containing wastewater, achieving the dual benefits of "hydrogen production + pollution control", which meets the needs of green chemical industry and environmental protection.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects: (1) The three-phase heterogeneous composite electrocatalyst prepared in this invention possesses excellent HER / UOR bifunctional electrocatalytic activity, and the kinetic rates of both types of half-reactions are significantly improved. In the HER reaction, a rate of 50 mA·cm⁻¹ is achieved in a 1.0 M KOH electrolyte. -2 100mA·cm -2 The overpotentials corresponding to the current density are only 50mV and 73mV, and the Tafel slope is as low as 49mV dec. -1 In the UOR reaction, within a 1.0 M KOH + 0.5 M urea electrolyte solution, at 10 mA·cm⁻¹ -2 At current density, the potential is only 1.29V vs RHE, and the Tafel slope is 42mVdec. -1 After constructing a two-electrode urea-assisted electrolysis hydrogen production system, 10 mA·cm -2 The tank voltage is only 1.32V; at 500mA·cm -2 Under industrial high current density conditions, the cell voltage can be reduced by 456mV compared to the traditional pure water OER electrolysis system, which significantly reduces the energy consumption for hydrogen production by electrolysis and simultaneously achieves urea wastewater degradation and green hydrogen preparation.
[0029] (2) The composite electrocatalyst of this invention possesses ultra-long stability suitable for high-current industrial applications. The catalyst is grown in situ on a nickel foam substrate without the addition of binders, and the nanorod array exhibits high bonding strength at the substrate interface. The three-phase Mott-Schottky heterojunction synergistically regulates the electronic structure, achieving HER at 1000 mA·cm⁻¹. -2 UOR at 500mA·cm -2 In the constant current long-term electrolysis test, the catalyst can operate stably and continuously for more than 100 hours. There is no obvious potential drift during the electrolysis process, no significant attenuation of the polarization curve before and after the test, and no obvious collapse of the catalyst structure is observed.
[0030] (3) The present invention has outstanding advantages in process and production cost. The present invention uses only inexpensive transition metal salts, industrial foam nickel, urea and other low-cost conventional raw materials, and does not require precious metal reagents such as Pt, Ru, Ir throughout the process; the preparation process only includes three simple steps: substrate pretreatment, hydrothermal synthesis of precursor, and high-temperature nitriding. The reaction conditions are mild and do not require expensive special equipment such as high pressure and ultra-high temperature. The whole process is easy to scale up for mass production, and the overall preparation cost is far lower than that of commercial precious metal catalysts. Attached Figure Description
[0031] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 The diagram shows the synthesis and structural characterization of MoN / WN / CoMoO4 / NF (corresponding to MoN / WN / CoMoO4 in the figure) in Example 1; where (a) is a schematic diagram of the preparation; (b) is the XRD pattern of the CoMoO4 / WO3 / NF precursor and MoN / WN / CoMoO4 / NF; (c, d) are the SEM images of MoN / WN / CoMoO4 / NF; (e) is the TEM image of MoN / WN / CoMoO4 / NF; (f, g) are the HRTEM lattice fringes of MoN / WN / CoMoO4 / NF; and (h) is the EDS elemental distribution map of MoN / WN / CoMoO4 / NF. Figure 2 The electronic structure analysis diagrams of X-ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS) of MoN / WN / CoMoO4 / NF prepared in Example 1 and MoN / NF, WN / NF, and CoMoO4 / NF prepared in Comparative Examples 1-3 are shown below. Among them, (a) is the full-spectrum XPS; (b-f) are the high-resolution XPS spectra of Co 2p, Mo 3d, W 4f, N 1s, and O 1s; (g-i) are the UPS spectra of CoMoO4, MoN, and WN. Figure 3 The HER performance analysis graphs are shown for the MoN / WN / CoMoO4 / NF prepared in Example 1 and the MoN / NF, WN / NF, CoMoO4 / NF, MoN / CoMoO4 / NF, 20wt.%Pt / C / NF and NF prepared in Comparative Examples 1-5, respectively; where (a) is the LSV polarization curve; (b) is the overpotential at different current densities (error bar: standard deviation, n=3); (c) is the Tafel plot; (d) is the EIS Nyquist plot; and (e) is the overpotential of MoN / WN / CoMoO4 at 1000 mA·cm⁻¹. -2 Stability testing; Figure 4 The table shows the UOR (Universal Oriented Resonance) performance analysis of MoN / WN / CoMoO4 / NF prepared in Example 1, and MoN / NF, WN / NF, CoMoO4 / NF, MoN / CoMoO4 / NF, RuO2 / NF, and NF prepared in Comparative Examples 1-4 and Comparative Example 6, respectively. (a) is the LSV curve comparing UOR and OER; (b) is the LSV curve; (c) is the Tafel plot; (d) is the Nyquist impedance spectrum; and (e) is the UOR / WN / CoMoO4 / NF at 500 mA·cm⁻¹.-2 The durability test lasted for 100 hours. Figure 5 The figures show the urea-assisted hydrogen production performance analysis of MoN / WN / CoMoO4 / NF prepared in Example 1 of this invention and MoN / NF, WN / NF, CoMoO4 / NF, and MoN / CoMoO4 / NF prepared in Comparative Examples 1-4, respectively. Among them, (a) is the LSV curve of urea electrolysis and conventional all-water electrolysis; (b) is the LSV curve; and (c) is the stability test of MoN / WN / CoMoO4 / NF. Figure 6 The contact angle is the MoN / WN / CoMoO4 / NF prepared in Example 1 of this invention. Detailed Implementation
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0034] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0035] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0036] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0037] This invention provides a MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst and its preparation method. The electrocatalyst uses nickel foam as a three-dimensional conductive self-supporting substrate, with cross-linked nanorods grown in situ on the substrate surface. The nanorods form a Mott-Schottky heterojunction interface from the three phases of CoMoO4, MoN, and WN. The preparation method includes three core steps: pretreatment of the nickel foam substrate, hydrothermal synthesis of a cobalt-molybdenum-tungsten composite oxide precursor, and high-temperature nitridation of urea to construct the three-phase heterojunction. This invention relies on the difference in work function between nitrides and oxides to construct a built-in electric field at the interface, significantly improving the interface charge transport efficiency; the cross-linked nanorods have a large electrochemical active area, exposing sufficient active sites. The self-supporting electrode obtained by this invention can simultaneously and efficiently catalyze the HER reaction at the cathode and the UOR reaction at the anode, is suitable for industrial-grade ampere-level high-current conditions, exhibits excellent long-term stability, uses inexpensive raw materials without precious metals, and has a simple process that is easy to mass-produce. It has extremely high industrial application prospects in the field of low-energy urea-assisted electrolysis for hydrogen production.
[0038] This invention provides a three-phase Mott-Schottky heterojunction electrocatalyst of MoN / WN / CoMoO4 / NF. The catalyst uses nickel foam as a conductive substrate, on which a nanorod array is grown in situ. The nanorods are composed of a CoMoO4 semiconductor phase, MoN and WN metal nitride phases. The Mott-Schottky heterojunction interface is constructed by the difference in work function between the nitride and the oxide, eliminating the need for a binder and ensuring a strong bond between the electrode and the substrate.
[0039] This invention also discloses a method for preparing the above-mentioned MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst, comprising the following steps: Step 1: Pretreatment of Nickel Foam Substrate Cut the nickel foam substrate and ultrasonically clean it sequentially with dilute hydrochloric acid, anhydrous ethanol, and deionized water to remove the oxide layer and oil impurities on the surface of the nickel foam. After cleaning, vacuum dry it (vacuum drying temperature set to 60~80℃) for later use to ensure that the cobalt-molybdenum-tungsten composite oxide precursor can grow uniformly in situ on the surface of the nickel foam.
[0040] Step 2: Preparation of CoMoO4 / WO3 / NF composite oxide precursor by hydrothermal method Molybdate, tungstate, and cobalt salt were prepared and dissolved in deionized water at a molar ratio of 1:(0.1~0.4):(0.1~0.4) (e.g., 1:0.25:0.25), and stirred thoroughly until completely dissolved. The pretreated nickel foam substrate was completely immersed in the above solution and sealed in a polytetrafluoroethylene-lined hydrothermal reactor. The reaction was carried out at a temperature range of 120~180℃ (e.g., 180℃) for 6~12h (e.g., 6h). After the reaction system cooled naturally, the product was washed sequentially with deionized water and anhydrous ethanol, and then dried under vacuum to obtain the CoMoO4 / WO3 / NF composite oxide precursor.
[0041] Step 3: High-temperature nitriding to construct a three-phase Mott-Schottky heterojunction self-supporting electrode The precursor prepared in step two and urea were placed together in a tube furnace and protected by inert nitrogen gas throughout the process. The heating rate was controlled at 3~5℃ / min (e.g., 5℃ / min), and the temperature was raised to 500~700℃ (e.g., 500℃) and nitrided at a constant temperature for 2~4h (e.g., 2h). After the system was naturally cooled to room temperature, the three-phase Mott-Schottky heterojunction electrocatalyst of MoN / WN / CoMoO4 / NF was obtained.
[0042] Urea, which serves as a nitrogen source, can also be replaced with ammonia.
[0043] A three-phase Mott-Schottky heterojunction electrocatalyst of MoN / WN / CoMoO4 / NF can be prepared using the above method.
[0044] This invention also provides a urea-assisted electrolysis hydrogen production two-electrode electrolysis system, in which the above-mentioned MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst is used as both the cathode and anode active electrode materials.
[0045] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.
[0046] All raw materials used in this invention were purchased from the market.
[0047] The technical solution of the present invention will be further illustrated by the following embodiments.
[0048] Example 1 A method for preparing a MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst includes the following steps: Step 1: Pretreatment of Nickel Foam Substrate Cut 20mm×20mm×1.5mm foam nickel, and ultrasonically clean it for 10 minutes each with 3M hydrochloric acid, anhydrous ethanol and deionized water to remove the surface oxide layer and oil stains. Then vacuum dry it at 70℃ for later use. Step 2: Preparation of CoMoO4 / WO3 / NF composite oxide precursor by hydrothermal method Take 1 mmol of ammonium molybdate ((NH4)6Mo7O) 24 0.25 mmol sodium tungstate (Na2WO4·2H2O) and 0.25 mmol cobalt nitrate (Co(NO3)2·4H2O) were dissolved in 30 mL of deionized water and stirred thoroughly until completely dissolved. The pretreated nickel foam obtained in step one was immersed in the solution and sealed in a 50 mL polytetrafluoroethylene-lined hydrothermal reactor. The reaction was carried out at 180 °C for 6 h. After the reaction system cooled naturally, the product was washed with deionized water and anhydrous ethanol in sequence, and then dried under vacuum to obtain the CoMoO4 / WO3 / NF composite oxide precursor. Step 3: High-temperature nitriding to construct a three-phase Mott-Schottky heterojunction self-supporting electrode The precursor prepared in step two was placed together with 0.5 g of urea in a tube furnace and protected by inert nitrogen gas throughout the process. The heating rate was controlled at 5 °C / min, and the temperature was raised to 500 °C and nitrided at a constant temperature for 2 h. After the system was naturally cooled to room temperature, a three-phase Mott-Schottky heterojunction electrocatalyst of MoN / WN / CoMoO4 / NF was obtained.
[0049] Comparative Example 1 Similar to Example 1, except that in step two, sodium tungstate and cobalt nitrate are not added, and the final MoN / NF electrocatalyst is prepared.
[0050] Comparative Example 2 Similar to Example 1, except that in step two, ammonium molybdate and cobalt nitrate are not added, and the WN / NF electrocatalyst is finally prepared.
[0051] Comparative Example 3 Similar to Example 1, except that sodium tungstate is not added in step two, and step three is omitted, and the final CoMoO4 / NF electrocatalyst is prepared.
[0052] Comparative Example 4 Similar to Example 1, except that sodium tungstate is not added in step two, and the final MoN / CoMoO4 / NF electrocatalyst is prepared.
[0053] Comparative Example 5 The preparation of a commercially available noble metal catalyst Pt / C / NF includes the following steps: Weigh 5.7 mg of commercial 20 wt.% Pt / C powder and disperse it in 1 mL of mixed solution (containing 80 μL Nafion solution, 260 μL anhydrous ethanol, and 660 μL deionized water); prepare a uniform catalytic ink by ultrasonic dispersion, drop-coat the ink onto a 20 mm × 20 mm × 1.5 mm nickel foam substrate, and dry at room temperature to obtain 20 wt.% Pt / C / NF.
[0054] Comparative Example 6 Similar to Comparative Example 5, except that Pt / C powder was replaced by RuO2 powder in equal mass to obtain RuO2 / NF.
[0055] Effect verification: (1) HER performance test: The three-phase Mott-Schottky heterojunction electrocatalyst prepared in Example 1 and the catalysts prepared in Comparative Examples 1 to 6 were used as working electrodes, Pt sheet as counter electrode and saturated Hg / HgO as reference electrode. The electrochemical performance was tested in a three-electrode system in 1.0M KOH electrolyte.
[0056] (2) UOR performance test: The three-phase Mott-Schottky heterojunction electrocatalyst prepared in Example 1 and the catalysts prepared in Comparative Examples 1 to 6 were used as working electrodes, Pt sheet as counter electrode and saturated Hg / HgO as reference electrode. The electrochemical performance was tested in a three-electrode system in 1.0M KOH + 0.5M urea electrolyte.
[0057] (3) Test of hydrogen production performance of urea-assisted electrolysis with two electrodes: The control electrodes of Example 1 and Comparative Examples 1 to 4 were used as cathodes and anodes respectively to construct a two-electrode system, and the electrochemical performance was tested in 1.0M KOH + 0.5M urea electrolyte.
[0058] Figure 1 The diagram shows the synthesis and structural characterization of MoN / WN / CoMoO4 / NF (corresponding to MoN / WN / CoMoO4 in the figure) in Example 1. (a) is a schematic diagram of the preparation process; (b) is the XRD pattern of the CoMoO4 / WO3 / NF (corresponding to CoMoO4 / WO3 in the figure) precursor and MoN / WN / CoMoO4 / NF; (c, d) are the SEM images of MoN / WN / CoMoO4 / NF; (e) is the TEM image of MoN / WN / CoMoO4 / NF; (f, g) are the HRTEM lattice fringes of MoN / WN / CoMoO4 / NF; and (h) is the EDS elemental distribution map of MoN / WN / CoMoO4 / NF. Figure 1The successful preparation of the three-phase heterojunction catalyst of this invention was confirmed. XRD patterns showed diffraction peaks of MoN and WN after nitridation of the precursor. SEM showed that the surface of the nickel foam was uniformly covered with a cross-linked nanorod array. TEM and HRTEM further confirmed the existence of clear heterojunction interfaces and lattice fringes inside the nanorods. EDS elemental distribution diagrams showed that Mo, W, Co, N, and O were uniformly distributed in the nanorods.
[0059] Figure 2 The X-ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS) spectra of MoN / WN / CoMoO4 / NF (corresponding to MoN / WN / CoMoO4 in the figure) prepared in Example 1 and MoN / NF (corresponding to MoN in the figure), WN / NF (corresponding to WN in the figure), and CoMoO4 / NF (corresponding to CoMoO4 in the figure) prepared in Comparative Examples 1 to 3 are shown. Among them, (a) is the full-spectrum XPS; (b-f) are the high-resolution XPS spectra of Co 2p, Mo 3d, W 4f, N 1s and O 1s; (g-i) are the UPS spectra of CoMoO4, MoN and WN. Figure 2 The electronic cooperation mechanism of the three-phase Mott-Schottky heterostructure was revealed. Compared with the single-component (MoN, WN, CoMoO4), the characteristic peaks in the XPS high-resolution spectrum of the three-phase composite material showed significant shifts. Electrons migrated from CoMoO4 to MoN / WN, resulting in a decrease in electron density on the CoMoO4 side (positive peak shift) and an increase in electron density on the nitride side (negative peak shift), indicating a redistribution of interfacial charges. The differences in work function among the components measured by UPS spectra confirmed the formation of the built-in electric field at the heterostructure interface, providing electronic structure-level evidence for directional charge migration and reaction kinetic optimization.
[0060] Figure 3 The graphs show the HER performance of MoN / WN / CoMoO4 / NF (corresponding to MoN / WN / CoMoO4 in the figure) prepared in Example 1, and MoN / NF (corresponding to MoN in the figure), WN / NF (corresponding to WN in the figure), CoMoO4 / NF (corresponding to CoMoO4 in the figure), MoN / CoMoO4 / NF (corresponding to MoN / CoMoO4 in the figure), 20wt.% Pt / C / NF (corresponding to Pt / C in the figure), and NF prepared in Comparative Examples 1-5, respectively. (a) is the LSV polarization curve; (b) is the overpotential at different current densities (error bar: standard deviation, n=3); (c) is the Tafel plot; (d) is the EIS Nyquist plot; and (e) is the overpotential of MoN / WN / CoMoO4 at 1000 mA·cm⁻¹. -2 Stability testing. Figure 3The catalyst in Example 1 demonstrates superior performance compared to the comparative catalyst and the commercial Pt / C benchmark in the hydrogen evolution reaction at the cathode. LSV curves and overpotential histograms show that at 50 mA·cm⁻¹… -2 and 100mA·cm -2 The overpotentials were only 50mV and 73mV, and the Tafel slope was 49mV dec. -1 The EIS shows the lowest charge transfer resistance, and it is at 1000 mA·cm⁻¹. -2 It can operate stably for more than 100 hours under ampere-level high current without significant degradation.
[0061] Figure 4 The figures show the UOR performance analysis of MoN / WN / CoMoO4 / NF prepared in Example 1 and MoN / NF, WN / NF, CoMoO4 / NF, MoN / CoMoO4 / NF, RuO2 / NF, and NF prepared in Comparative Examples 1-4 and Comparative Example 6, respectively. (a) is the LSV curve comparing UOR and OER; (b) is the LSV curve; (c) is the Tafel plot; (d) is the Nyquist impedance spectrum; and (e) is the UOR / WN / CoMoO4 / NF at 500 mA·cm⁻¹. -2 The durability test lasted for 100 hours. Figure 4 This demonstrates that the catalyst in Example 1 of the present invention exhibits low-potential start-up, fast reaction kinetics, and ultra-long-term stability in the anodic urea oxidation reaction. UOR start-up potential (10 mA·cm⁻¹) -2 The voltage drop (1.29V vs. RHE) is significantly lower than that of the conventional OER, and the Tafel slope (42mV dec) is much lower. -1 The EIS impedance is at its minimum value, and it is at 500 mA·cm. -2 After 100 hours of constant current electrolysis, there was no significant potential drift.
[0062] Figure 5 The figures show the urea-assisted hydrogen production performance analysis of MoN / WN / CoMoO4 / NF prepared in Example 1 of this invention and MoN / NF, WN / NF, CoMoO4 / NF, and MoN / CoMoO4 / NF prepared in Comparative Examples 1 to 4, respectively. Among them, (a) is the LSV curve of urea electrolysis and conventional all-water electrolysis; (b) is the LSV curve; and (c) is the stability test of MoN / WN / CoMoO4 / NF. Figure 5 This demonstrates that the catalyst of this invention possesses significant energy-saving advantages in practical urea-assisted electrolysis hydrogen production systems. When this catalyst is used as both the anode and cathode, the total electrolysis LSV curve in a urea-containing electrolyte is much lower than that of the traditional all-water electrolysis curve, at 500 mA·cm⁻¹. -2 The cell voltage is reduced by 456mV under industrial-grade current density, and it exhibits excellent structural and performance stability during long-term constant current electrolysis.
[0063] Figure 6 The figure shows the contact angle of the MoN / WN / CoMoO4 / NF prepared in Example 1 of this invention. As can be seen from the figure, the material has superhydrophobicity.
[0064] In summary, Figure 1 The evidence was successfully synthesized. Figure 2 Revealing the root of high-performance electronic structure, Figure 3 and Figure 4 Its high catalytic activity and industrial-grade stability in the HER and UOR half-reactions were verified respectively. Figure 5 This confirms that it can achieve significant energy savings in actual two-electrode electrolysis systems. Figure 1-5 This fully supports the technological advancement and industrial application prospects of the three-phase Mott-Schottky heterojunction electrocatalyst of this invention in the field of low-energy consumption, long-life urea-assisted hydrogen production.
[0065] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst, characterized in that, Using nickel foam as a conductive substrate, an array of nanorods is grown in situ on the surface of the conductive substrate; the nanorods are composed of CoMoO4 semiconductor phase, MoN and WN metal nitride phase, and the Mott-Schottky heterostructure is constructed by the difference in work function between the nitride and the oxide.
2. The MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst according to claim 1, characterized in that, The nanorod array is a cross-linked nanorod array, possessing a porous structure and superhydrophilic properties.
3. A method for preparing a MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst as described in any one of claims 1 to 2, characterized in that, Includes the following steps: (1) Cut the nickel foam substrate, and clean it with dilute hydrochloric acid, anhydrous ethanol and deionized water in sequence to remove the oxide layer and oil stains on the surface of the nickel foam, and then vacuum dry it. (2) Dissolve molybdate, tungstate and cobalt salt in deionized water and stir thoroughly until completely dissolved to obtain a mixture; completely immerse the pretreated nickel foam substrate from step (1) in the mixture and then place it in a reactor for hydrothermal reaction. After the reaction is completed, cool naturally to room temperature and wash the product with deionized water and anhydrous ethanol in sequence. After vacuum drying, obtain the CoMoO4 / WO3 / NF composite oxide precursor. (3) The CoMoO4 / WO3 / NF composite oxide precursor obtained in step (2) is placed together with urea in the reaction zone of a tube furnace. High-purity nitrogen is introduced throughout the process to maintain an inert protective atmosphere for high-temperature nitriding. After cooling, the MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst is obtained.
4. The preparation method according to claim 3, characterized in that, In step (1), the ultrasonic cleaning time for dilute hydrochloric acid, deionized water, and anhydrous ethanol is 10 min; the vacuum drying temperature is 60~80℃.
5. The preparation method according to claim 3, characterized in that, In step (2), the molar ratio of molybdate, tungstate, and cobalt salt is 1:(0.1~0.4):(0.1~0.4).
6. The preparation method according to claim 5, characterized in that, The molybdate is ammonium molybdate, the tungstate is sodium tungstate, and the cobalt salt is cobalt nitrate.
7. The preparation method according to claim 3, characterized in that, In step (2), the temperature of the hydrothermal reaction is 120~180℃ and the reaction time is 6~12h.
8. The preparation method according to claim 3, characterized in that, In step (3), the heating rate during the high-temperature nitriding process is 3~5℃ / min, the holding temperature is 500~700℃, and the holding time is 2~4h.
9. A urea-assisted electrolysis hydrogen production two-electrode electrolysis system, characterized in that, The MoN / WN / CoMoO4 / NF three-phase Mott-Schottky heterojunction electrocatalyst described in any one of claims 1 to 2 is used as both the cathode and the anode.
10. The urea-assisted electrolysis hydrogen production two-electrode electrolysis system according to claim 9, characterized in that, The two-electrode electrolysis system is electrolyzed in an alkaline electrolyte containing urea, with hydrogen evolution occurring at the cathode and urea oxidation occurring at the anode.